TERAPI BERMAIN ORIGAMI TERHADAP KECEMASAN ANAK USIA PRASEKOLAH (3-6 TAHUN) YANG MENJALANI HOSPITALISASI - Al-Ihsan, Muhammad; Santi, Eka; Setyowati, Anggi (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2018)
Hospitalization can cause anxiety responses among preschool age children. Impact of children'sanxiety when undergoing hospitalization may interfere with growth and development, healingprocess, and trauma. Origami therapy is one of the interventions to reduce anxiety amongchildren during their hospitalization. The objective of this study was to measure the effectivenessof origami therapy on the anxiety among preschool children (3-6 years) during hospitalizatioIdaman Banjarbaru Public Hospital. The Method this study was quasi-experimental with nonequivalent pretest posttest control group design. The consecutive sampling technique was usedin this study to select the samples of 30 preschool children, divided into 15 intervention groupand 15 control group. Measurement of anxiety preschoolers using Preschool Anxiety Scale. TheResults Analyzed using non-parametric test Wilcoxon Signed Rank Test, there was an effect oforigami therapy on the anxiety preschool age children during Hospitalization at IdamanBanjarbaru Public Hospital (p-value 0.001).